2023
DOI: 10.1097/md.0000000000033473
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the prevention and treatment of postoperative delirium by acupuncture: A review

Abstract: Postoperative delirium is a common postoperative complication of neurocognitive dysfunction, especially in elderly surgical patients. Postoperative delirium not only damages patients’ recovery but also increases social costs. Therefore, its prevention and treatment has essential clinical and social significance. However, due to its intricate pathogenesis and limited pharmacological interventions, the effective prevention and treatment of postoperative delirium remains a thorny problem. As traditional acupunctu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown the beneficial effects of acupuncture on the treatment of chronic pain, such as osteoarthritis, back pain, neck pain, headaches [14], and post-operative pain [15]. It is particularly noteworthy that acupuncture has a long-lasting and preventive effect [16][17][18][19]. A meta-analysis found that the effect of a single course of acupuncture therapy for patients with chronic pain did not appear to decrease significantly over 12 months [19].…”
Section: A Related Workmentioning
confidence: 99%
“…Numerous studies have shown the beneficial effects of acupuncture on the treatment of chronic pain, such as osteoarthritis, back pain, neck pain, headaches [14], and post-operative pain [15]. It is particularly noteworthy that acupuncture has a long-lasting and preventive effect [16][17][18][19]. A meta-analysis found that the effect of a single course of acupuncture therapy for patients with chronic pain did not appear to decrease significantly over 12 months [19].…”
Section: A Related Workmentioning
confidence: 99%